Fashioning the Face: Sensorimotor Simulation Contributes to Facial Expression Recognition. Issue 3 (March 2016) - Wood, Adrienne; Rychlowska, Magdalena; Korb, Sebastian; Niedenthal, Paula
Abstract : When we observe a facial expression of emotion, we often mimic it. This automatic mimicry reflects underlying sensorimotor simulation that supports accurate emotion recognition. Why this is so is becoming more obvious: emotions are patterns of expressive, behavioral, physiological, and subjective feeling responses. Activation of one component can therefore automatically activate other components. When people simulate a perceived facial expression, they partially activate the corresponding emotional state in themselves, which provides a basis for inferring the underlying emotion of the expresser. We integrate recent evidence in favor of a role for sensorimotor simulation in emotion recognition. We then connect this account to a domain-general understanding of how sensory information from multiple modalities is integrated to generate perceptual predictions in the brain. Trends: People's recognition and understanding of others' facial expressions is compromised by experimental (e.g., mechanical blocking) and clinical (e.g., facial paralysis and long-term pacifier use) disruptions to sensorimotor processing in the face. Emotion perception involves automatic activation of pre- and primary-motor and somatosensory cortices, and the inhibition of activity in sensorimotor networks reduces performance on subtle or challenging emotion recognition tasks. Sensorimotor simulation flexibly supports not only conceptual processing of facial expression but also, through cross-modal influences on visual processing, the building of a complete percept of the expression. While automatic and presumably nonconscious, sensorimotor simulation of facial expressions is modulated by the perceiver's social context and motivational state.